2018
DOI: 10.1177/0269215518788615
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic auditory stimulation for reduction of falls in Parkinson’s disease: a randomized controlled study

Abstract: RAS training significantly reduced the number of falls in Parkinson's disease and modified key gait parameters, such as velocity and stride length.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(99 citation statements)
references
References 29 publications
0
90
0
9
Order By: Relevance
“…The decrease of stride length is contrary to studies using rhythmic auditory stimulation on persons with Parkinson’s disease. 44 Yet, the previous studies did not compare different walking percentages as presented in this study, and therefore direct comparisons cannot be made.…”
Section: Discussionmentioning
confidence: 84%
“…The decrease of stride length is contrary to studies using rhythmic auditory stimulation on persons with Parkinson’s disease. 44 Yet, the previous studies did not compare different walking percentages as presented in this study, and therefore direct comparisons cannot be made.…”
Section: Discussionmentioning
confidence: 84%
“…A recent review (Ginis et al, 2017) also concluded that cue-augmented training can reduce the severity of freezing in PD patients, but limitations in long-term consolidation and transfer of the effects to untrained tasks need to be considered in this population. RAS has been also recently applied to reduce falls or risk of falls in healthy elderly (Hurt-Thaut, 2014) and PD patients (Thaut et al, 2018). These studies collectively found that RAS training significantly reduced the number of falls in healthy individuals and PD patients by modifying key kinematics in gait control, thus suggesting that RAS may be beneficial to address the risk of falls.…”
Section: Resultsmentioning
confidence: 99%
“…of gait function with supporting evidence from randomized control trials and studies in Parkinson's disease (Cubo et al, 2004;Murgia et al, 2018;Thaut et al, 2019), stroke (Thaut et al, 2007;Cha et al, 2014;Mainka et al, 2018;Elsner et al, 2020), cerebral palsy (Kim et al, 2012;Wang et al, 2013), and multiple sclerosis (Seebacher et al, 2017). RAS is supported by numerous lines of fundamental neuroscience evidence, including a recent finding that RAS attenuates dopamine response in younger adults (Koshimori et al, 2019).…”
Section: Non-sensorimotor Techniques Are Transferable From In-person mentioning
confidence: 90%